The use of artificial intelligence for analysing the impact of Military Technical Cooperation on political alliance establishment in XX-XXI centuries - Iryna Alieksieienko; Stepan Huta; Andrii Bohuslavets; Olena Derkach; Oleksandr Derkach (Clío)
The aim of the study is to determine the influence of Military Technical Cooperation (MTC) on establishing of the MPAs through the analysis of historical data and key political, economic, military, and socio-cultural factors, taking into account the geopolitical context and strategic interests of states. The study employed the following methods: identification of key influencing factors, multifactor analysis, retrospective analysis, correlation convergent comparative analysis, artificial intelligence (AI)-based analysis. The study confirmed that MTC is not a sufficient condition for establishing of the MPAs, and its influence is determined by a combination of political, economic, military, and socio-cultural factors. AI-based analysis was used to process 20+ datasets covering over 200 years of historical data and 3,500+ states. Correlation convergence comparative analysis showed that establishing of the MPAs more often depends on the strategic interests of states than on the MTC.